2022
DOI: 10.1021/acsami.2c07263
|View full text |Cite
|
Sign up to set email alerts
|

Scalable 3D Honeycombed Co3O4 Modified Separators as Polysulfides Barriers for High-Performance Li–S Batteries

Abstract: Lithium sulfur batteries (LSBs) are regarded as one of the most promising energy storage devices due to the high theoretical capacity and energy density. However, the shuttling lithium polysulfides (LiPSs) from the cathode and the growing lithium dendrites on the anode limit the practical application of LSBs. To overcome these challenges, a novel three-dimensional (3D) honeycombed architecture consisting of a local interconnected Co3O4 successfully assembled into a scalable modified layer through mutual suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…In contrast, the SWCNT/PP and COF-PDA/PP cells suffered from poorer capacity retention, which was 424 and 328 mAh g –1 , respectively. The performances delivered by the COF-PDA/SWCNT/PP cell also revealed great competitiveness with the recent studies relating to functional-separator engineering (Table S2), ,, which further demonstrated the extremely attractive advantage of such separator design for performing improvement of Li–S batteries. The enhancements in the capacity, rate performance, and cycling ability resulted from the highly conductive nature, fast charge/mass transportation, and high LiPSs affinity of the as-developed COF-PDA/SWCNT modification layer, which immobilized LiPSs species and effectively catalyzed their conversion, resulting in effective inhibition of the shuttle effect and the resultant enhancement in the battery performance.…”
Section: Resultsmentioning
confidence: 69%
“…In contrast, the SWCNT/PP and COF-PDA/PP cells suffered from poorer capacity retention, which was 424 and 328 mAh g –1 , respectively. The performances delivered by the COF-PDA/SWCNT/PP cell also revealed great competitiveness with the recent studies relating to functional-separator engineering (Table S2), ,, which further demonstrated the extremely attractive advantage of such separator design for performing improvement of Li–S batteries. The enhancements in the capacity, rate performance, and cycling ability resulted from the highly conductive nature, fast charge/mass transportation, and high LiPSs affinity of the as-developed COF-PDA/SWCNT modification layer, which immobilized LiPSs species and effectively catalyzed their conversion, resulting in effective inhibition of the shuttle effect and the resultant enhancement in the battery performance.…”
Section: Resultsmentioning
confidence: 69%
“…They found that the −O-terminated group can entrap the shorter chain of sulfides, whereas the longer chain can be entrapped by the −OH group of MXene. Many scientists have also used the MXene composite strategy to improve the performance of batteries. , MXene has polar properties and functional groups, which are the perfect candidate to hybridize with carbon nanotubes to form an MXene–CNT composite. Carbon nanotubes can help to increase the surface area and maintain the structural reliability of the composite.…”
Section: Applications Of Mxenesmentioning
confidence: 99%
“…Even with a small load (0.265 mg/cm 2 ) of COF−SO 3 H material, the electrochemical performances (1163.4 mA h/g over 100 cycles at 0.2 C) are still superior to those of other materials such as inorganic materials (1007 mA h/g over 100 cycles at 0.1 C with a load of 0.49 mg/cm 2 ) and MOF-modified separators (585.4 mA h/g even after 300 cycles at 0.5 C with a load of 0.33 mg/cm 2 ). 39,40 Besides, in the twostep discharge process, there is a high-discharge plateau related to the formation of high-order soluble polysulfides and a lowdischarge plateau reflecting the generation of insoluble Li 2 S 2 and Li 2 S. 14 The capacity of high voltage (Q H ) represents the reversible electrochemical behavior (2Li + + S 8 ↔ Li 2 S 8 ) and brings a relatively invariable capacity, and the practical promotion of capacity is mainly dependent on the enhanced performance in the region of low voltage (Q L ). Figure 4f is drawn for better understanding of this modification of the capacity in the area of Q H or Q L .…”
Section: ■ Introductionmentioning
confidence: 99%